Investigation of the effects on ink colour of lacquer coating applied to the printed substrate in the electrophotographic printing system - SÖNMEZ, SİNAN (SCIENDO, 2021)
In this study, the effects of the lacquer applied to the printing materials which were printed by electrophotographic printing method on printing quality were investigated. In practice, printing materials with the same weight and different optical properties were used and the study was carried out in three stages. The optical and physical properties of the printing materials used in the first part were determined, in the second part, the printing of these materials by electrophotographic printing method and printability tests were performed. In the third chapter, matte and glossy lacquers were applied to these printed materials and printability tests were repeated. As a result of the study, it was observed that the application of gloss and matte lacquer caused a decrease in the printing density values and also the application of matte lacquer caused a decrease in the gloss values.
Keywords: Lacquer; Gloss; Printing; Paper; Electrophotography; GLOSS